CATENATION OF BSE AND NSE - ., Reepu (International Journal of Advanced Science and Technology, 2019)
Stock Exchanges are the vitals of an economy. Bombay Stock Exchange and National Stock Exchange provides an effective platform to exchange the securities. Marked by distinct rules, they drive an automated system with an objective of investor protection. Further, their objective is to attain an international level. The present paper is an attempt to understand the correlation, co-integration between NSE and BSE. Moreover, emphasis is also laid on the understanding between the up and down movements of share price. Tools Pearson correlation, Unit root test and johnson co-integration test have also been employed. Study concludes that there exists a strong correlation between the two existing variables.